Ostracized lower caste and silenced women- hood in Ponthanmada - A, VEENA (International Journal of Psychosocial Rehabilitation, 2020)
The term “subaltern” refers to any person or group of inferior rank and station whether in terms of race, class, gender, sexual orientation, ethnicity or religion. It also refers to lower strata people of illiterate peasantry, non-elite cultural groups who are under-represented, under-taught, non-canonical and the subordinated group who are always directly or indirectly influenced by ideologies of dominant class. In literature, it has become the most discussed and exploring area. In India, the term got its prominence and exposure in its full fetched form say after colonization. Women, Dalit, rural, tribal, immigrant labourers are the major categories taken into consideration under Subaltern. Indian literature and films possess a pivotal role in representing the subaltern issues and often eligible even to compete with international products of arts and literature. Almost all of the Indian languages have worked in subaltern literature – some spoke for them and some for themselves.Recently the postcolonial traits in subaltern studies are widely discussed both at academic and cultural strata. Some of the recurring works commented in this contexts are Mulk Raj Anand’s Untouchable, Coolie, Salman Rushdie’s Midnight’s Children, translations like Poisoned Bread: Translations from Modern Marathi DalitLiterature, PerumalMurugan’sOne Part Women, the novels of Aashapurna Debi andJayamohan’sNooruSimhasanangal.Indian film industry too had produced innumerable examples on this context. Some of the notable and most discussed ones are Bayen, Kancheepuram, Slum Dog Millionaire, and from Malayalam industry the chain continues through Vigathakumarantill Pappilio Buddha. This paper intends to anatomise or examine the subaltern representations in the Malayalam movie Ponthanmada, a 1994 Malayalam film directed by T V Chandran. The film portrays the ostracised and exploited lower class and silenced womanhood, sometimes back in the history and of course a realization that the contemporary time is in no way better than the past except some alterations in the way it express – as old wine in new bottle.